Clinical impact of rapid bacterial identification by MALDI-TOF MS combined with the bêta-LACTA™ test on early antibiotic adaptation by an antimicrobial stewardship team in bloodstream infections. Issue 9 (2nd September 2018) - Mizrahi, A.; Amzalag, J.; Couzigou, C.; Péan De Ponfilly, G.; Pilmis, B.; Le Monnier, A.
Abstract: Background: Bloodstream infections (BSI) can potentially be life-threatening infections and are associated with a high crude mortality, moreover with an inappropriate first-line antibiotic therapy. Bacterial resistance is more and more frequently observed. New strategies of BSI management are urgently needed. Materials and methods: During an 18-months period, we prospectively evaluated the clinical impact of rapid bacterial identification by MALDI-TOF MS technology combined with an antimicrobial stewardship team (AST) intervention. Furthermore, during an 8-months period, we combined this strategy with the rapid detection of third-generation cephalosporin (3GC) resistance by the Bêta-LACTA™ test (BLT) directly on blood cultures. We then evaluated the theoretical impact of BLT on antibiotic therapy adaptation and establishment of infection control measures. Results: A total of 335 blood cultures were enrolled during the study. MALDI-TOF MS gave accurate identification for 301 blood cultures (89, 8%) and led to early antibiotic therapy adaptation for 73 episodes (21.8%). BLT was performed on 141 blood cultures, revealing 28 3GC-resistant bacteria (19.9%). Twenty-one patients (75%) received a non-adapted first-line treatment. The antibiotic therapy adaptation was delayed by 28.1 hours and the establishment of infection control measures by 35 hours with antimicrobial susceptibility testing, compared to the theoretical adaptation with BLT result. Conclusions: These tools can be included in a strategy of bloodstream infections management for a better patient care, optimizing and saving the use of antibiotics, notably carbapenems as well as diminishing the spread of multi-drug resistant bacteria by applying rapidly infection control measures.